Antibiofilm Effect of Rambutan Leaf Extract (Nephelium lappaceum L.) on Selected Periodontal Pathogens - Maulina, Syarifah Aulia; Soulissa, Abdul Gani; Widyarman, Armelia Sari (Journal of Indonesian Dental Association, 2022)
Introduction: In Indonesia, periodontal disease is one of the dental and oral diseases with the highest prevalence. Bacteria in subgingival plaque can cause periodontal disease, such as Porphyromonas gingivalis and Fusobacterium nucleatum. Herbal medicine has potential as an alternative in the treatment of periodontal disease, for example, rambutan leaves (Nephelium lappaceum L.) are known to have antibacterial properties because they contain flavonoids, tannins, and saponins. Objective: To determine the effects of rambutan leaf extract (Nephelium lappaceum L.) on development of Porphyromonas gingivalis and Fusobacterium nucleatum biofilms. Methods: This study was carried out using the biofilm assay method with crystal violet staining and rambutan leaf extract (Nephelium lappaceum L.) with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, and 3.125% were used as the test material. A microplate reader with a wavelength of 490 nm was used to measure the biofilm density of Porpyromonas gingivalis ATCC 33277 and Fusobacterium nucleatum ATCC 25586. The data obtained were then analyzed statistically using one-way analysis of variance (ANOVA), with a significance level of p<0.05. Results: The most effective concentration of rambutan leaf extract for inhibiting biofilm development at 24 hours incubation was a 100% concentration with an average optical density (OD) of 0.147 against Porphyromonas gingivalis and a 100% concentration with an average OD of 0.077 against Fusobacterium nucleatum. Conclusion: Rambutan leaf extract (Nephelium lappaceum L.) is capable of inhibiting the development of Porphyromonas gingivalis and Fusobacterium nucleatum biofilms, respectively.